2020
DOI: 10.1002/ejic.202000275
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogen Bonding Induced Tetraselenides from Twisted Diselenides

Abstract: The first sterically controlled oxidation of mesoionic selone using copper(II) salt was demonstrated. The present methodology gave access to a rare tetraselenide from dimerized diselenides through chalcogen bonding (ChB). Besides, a similar approach with sterically less crowded mesoionic triazole [a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Most likely, dimerization of the selenium adducts occurs (Scheme 1), which has been proposed [8] and observed before for NHC sulfur adducts, [9] and during electrochemical synthesis of disulfides [10] . Recently, 1,2,3‐triazolin di‐ and tetraselinides have been isolated after chemical oxidation [11] …”
Section: Resultsmentioning
confidence: 64%
“…Most likely, dimerization of the selenium adducts occurs (Scheme 1), which has been proposed [8] and observed before for NHC sulfur adducts, [9] and during electrochemical synthesis of disulfides [10] . Recently, 1,2,3‐triazolin di‐ and tetraselinides have been isolated after chemical oxidation [11] …”
Section: Resultsmentioning
confidence: 64%
“…The sterically controlled oxidation of the triazoline selones 183 in the presence of a copper­(II) salt yielded MIC-stabilized di- and tetraselenides (Scheme ). The reaction product is probably dependent on the steric bulk of the MIC substituents. The MIC selenium adducts were also investigated via 77 Se NMR spectroscopy to gauge the π-acceptor properties of the corresponding triazolylidenes (see section on donor/acceptor properties above). , Furthermore, the electrochemical properties of the MIC selenium adducts were investigated, and it was shown that, with appropriate substituents, reduction of these adducts, which are triazolylidene-based, is reversible.…”
Section: Main Group Educts Of Micsmentioning
confidence: 89%
“…The sterically controlled oxidation of the triazoline selones 183 in the presence of a copper(II) salt yielded MIC-stabilized di-and tetraselenides (Scheme 38). 146 The reaction product is probably dependent on the steric bulk of the MIC substituents. The MIC selenium adducts were also investigated via 77 Se NMR spectroscopy to gauge the π-acceptor properties of the corresponding triazolylidenes (see section on donor/acceptor properties above).…”
Section: Group 16mentioning
confidence: 99%
“…One might expect either aurophilic [11] Au … Au or chalcogenophilic [12] Se … Se intermolecular bonding for these di/mono‐cationic Se/Au species 2 b , 3 and 4 , however, no such intermolecular secondary bonds were observed (compare Supporting Information), most likely due to the position of the tetraphenylborate or hexafluoridophosphate counterions in the crystal lattice. In comparison, NHC−Se gold(I) complexes containing bulky wingtip substituents display dimeric solid state structures with weak Se … Se interactions [10a] …”
Section: Methodsmentioning
confidence: 99%
“…In comparison, NHC−Se gold(I) complexes containing bulky wingtip substituents display dimeric solid state structures with weak Se … Se interactions. [10a] …”
mentioning
confidence: 99%